IDENTIFIKASI NILAI KALOR BIOCHAR DARI TONGKOL JAGUNG DAN SEKAM PADI PADA PROSES PIROLISIS - Iskandar, Taufik (Jurnal Teknik Kimia, 2012)
Process pirolisis can alter yielded by biomassa waste at various agriculture waste and agroindustri become valuable product sell highly, easy to in operation, friendly of high environmental security standard and environment. This research aim to to identify optimal kalor value of biochar to different temperature influence at pyrolisis process with perception. Variable pyrolisis temperature are (400, 450, 500, 550, 600) 0C, and biomassa waste types (rise husk and cob). Pursuant to result of research which have been done/conducted hence optimal Value kalor of biochar rise husk at temperature 500 0C equal to 7111 cal/ gr, cob is at temperature 500 0C kalor value 3705 cal/gr. So that can be concluded that difference assess kalor at biochar product very is base on of bait type/pirolisis temperature and materials. Thereby cob biochar can be recommended upon which burn alternative pyrolisis process at temperature 500 0C because will yield biochar with high kalor value and also rate irrigate and low dusty rate. Key words: biochar, biomassa, Caloric value,  pyrolysis process